Clinical prognostic factors and outcomes of essential thrombocythemia when transformed to myelodysplastic syndromes and acute myeloid leukemia. (March 2016) - Suleiman, Yaman; Dalia, Samir; Liu, Jane Jijun; Bowers, Jeremy W.; Padron, Eric; Lancet, Jeffrey E.; Fulp, William; Moscinski, Lynn C.; Komrokji, Rami S.; Zuckerman, Kenneth S.; Zhang, Ling
Highlights: It is rare for patients with ET to transform to MDS or AML. Given the rarity, the risk factors for transformation are understudied. Age, myelofibrosis & leukocytosis are associated with lower overall survival at transformation. A large study cohort is necessary to explore the molecular profiles leading to the transformation. Abstract: Transformation of essential thrombocythemia (ET) to myelodysplastic syndromes or acute myeloid leukemia is infrequent, comprising 1–5% of cases with dismal clinical outcome. Studies on prognosis in ET patients with leukemic transformation are limited. The large cohort included 40 patients (1990–2014) with ET transformation (median age of 59 years, M:F of 1:1). Median time from ET diagnosis to transformation was 76 months (26–481) with median follow-up time of 15 years. Advanced age, myelofibrosis (grade 2–3), and leukocytosis at the time of transformation were associated with inferior OS from transformation ( p  < 0.05). Given rarity of the clinical scenario, multicenter efforts are encouraged.